Al-Ma’alim al-Manhajiyah Fi Dirasati al-Qadhaya Al-Qur’aniyah ‘Inda al-Faruqi wa al-‘Attas - Rochmad Rochmad; Radwan Jamal Yousef Elatrash (Universitas Darussalam Gontor, 2024)
Ismail Raji al-Faruqi and Sayyid Muhammad Naquib al-Attas were the founders of the Islamization of Knowledge movement. As Muslim philosophers, both have their own methods in formulating thoughts that originate from the Qur’an and Sunnah. So this research tries to reveal the method of Ismail Raji al-Faruqi and Sayyid Muhammad Naquib al-Attas in revealing the meanings contained in the verses of the Qur'an. This research uses a descriptive analysis method to compare the interpretation methods used by al-Faruqi and al-Attas. Among the conclusions of this research is that al-Faruqi uses an axiological approach in interpreting the Qur'an, where the verses of the Qur'an have a multi-level axiological value. Whereas al-Attas uses a semantic approach in interpreting the verses of the Qur'an and refers to elements of bil ma'tsur such as the Hadith of the Prophet SAW.